ANALISIS PENDAPATAN DAN PERSEPSI PETANI TERHADAP KEMITRAAN USAHA KAMPUNG KUCAI DI KABUPATEN BLITAR - Brillian Pintakami, Lintar; Wahyu Budiman, Eko (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
This study aims to describe the agribusiness partnership process that takes place in Kampung Kucai, analyze the income of chives farming, and the perception of chives farmers on the partnership process in Garum District, Blitar Regency. This research uses a qualitative approach in the form of a case study. Informants in this study were partner chives farmers in Kampung Kucai. Determination of the sample of plasma partner farmers was carried out by purposive sampling method. Informants were selected based on secondary data from the core and information from farmers. So the sample used for Kucai Mitra farmers is 20 people. In addition, there are also 5 key informants. The methods of data collection carried out in this study are of several types, namely structured interviews, in-depth interviews, participatory observations, and documentation. The data analysis method used in this researchis descriptive analysis, income analysis, and Likert analysis. The results showed that the type of partnership between the Financial Institution "Bank BRI" and the partner chives farmers was classified as a nucleus-plasma partnership pattern. In the mechanism of the partnership pattern of the Financial Institution "BRI Bank" with the Kucai Farmer Group, it is carried out based on a partnership agreement. The agreement letter contains the identities of the two partnering parties and the rules given by "Bank BRI" as well as the location or planting area. The total income from chives farming is Rp. 242,000, -. The income of chives farming can be taken by women farmers once a month at the monthly member meeting in the Women Farmers Group or can be saved in advance. If they are saved, usually the women farmers in the research location will take the income before the Eid al-Fitr. The perception of partner chives farmers on the planning of partnership implementation is 80% or very good, the perception of partner chives farmers on the partnership process is 78% or quite good, and the perception of the evaluation of the partnership is very good with 85% results. So that the results of the Likert analysis on the average perception of partner chives farmers on the partnership process with financial institutions "Bank BRI" have a very good category with a percentage of 80% where the total score is 483.